L'excursion Géologique de l'I.G.C.P. dans l'Anti-Atlas Marocain, Mai 1973 - Church, W.; Young, G. (Geoscience Canada, 1974)
Summary An I.G.C.P. group, in May of 1973 had the opportunity of visiting the Anti-Atlas of Morocco. The object of the excursion was to visit four of the Precambrian inliers of the Anti-Atlas to see the bases on which Choubert and Faure-Muret have established a stratigraphy for this very complex region. Another goal was to make comparisons with the Precambrian of SW. Europe and the Canadian Shield. This brief report on the excursion points out the many remarkable similarities between the history of the Moroccan Anti-Atlas and the eastern part of the Canadian Shield. Attention is also focussed on a possible occurrence of early Proterozoic oceanic crust in the Anti-Atlas.